CACAni : cel shader - Cheng, Wei Jie. (2010)
With current advanced computer graphics technology, people have grown accustomed to graphical images seen in their daily life, especially in the field of video games and animations. Many shading techniques have been developed to suit different demands in their respective industries. An application using X-Toon Shading will be written to provide a means to help animators and artists to reduce the work required to texture their models manually. This project will focus on the insight of the research on X-Toon Shading as well as its implementation and the development made during the project lifespan. Various considerations such as lighting, material, computational formula and texture map were taken into account when implementing X-Toon Shading. It has been concluded that X-Toon shading is a viable computer aid for artists to render textures and improvements can be made to bring the application to a higher level.